Dental age estimation in a group of Kenyan children using Willems' method: a radiographic study - Eunice Njeri Kihara; Peter Gichangi; Helen M. Liversidge; Fawzia Butt; Gichambira Gikenye (Taylor & Francis Group, 2017)
Background: Radiographic study of developing teeth provides a reliable indication of chronological age. In Kenya, dentists are often required to estimate age. However, there is a paucity of publications on the performance of dental age estimation methods. Aim: To determine the accuracy of Willems' method of dental age estimation. Subjects and methods: A cross-sectional study was done at The University of Nairobi Dental Hospital. Panoramic radiographs of children aged 3.00-16.99 years old were studied. Dental age was estimated according to Willems' method and compared to chronological age and the difference compared to zero using a t-test. Results: Radiographs of 187 (47%) females and 214 (53%) males were analysed. Willems' method significantly over-estimated the mean overall age by -0.24 ± 1.17 years (p < .000). Age was over-estimated in girls by -0.10 ± 1.18 years (p = .254); however, age in boys was significantly over-estimated by -0.37 ± 1.14 years (p < .000). Conclusions: Willem's model over-estimated dental age slightly and the method performed better in estimating the age of girls compared to boys. The majority of the children had their age estimated within 1 year of their chronological age. This suggests that Willems' method is suitable for estimating the ages of individual children in Kenya.